Pemahaman Guru Fikih terhadap Talfiq Al-Mazhab dalam Pelaksanaan Shalat di Pondok Pesantren Modern Rahmatul Asri - Nurhajrahwati; Bakry, Muammar (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This paper aims to discuss the analysis of talfiq al-Mazhab for the implementation of prayer and ablution, this study uses a descriptive (qualitative) field study. The results of this study indicate that: in the implementation of worship there is no problem with talfiq (mixing one school with another in the case of worship). religion, especially in terms of worship), but when performing a prayer service using the Shafi'I School and when performing ablution using the Hanafi School, the talfiq issue is not a problem. So, in the fiqh teacher's understanding of talfiq al-Mazhab in the implementation of prayer and ablution at the Rahmatul Asri Modern Islamic Boarding School, it is "allowed". The application of schools of thought at the Rahmatul Asri Modern Islamic Boarding School in general in carrying out their worship using the Syafi'i School does not mean that they are fanatical in one school only and follow those in accordance with the Qur'an and As-Sunnah. However, in the fiqh approach, the teachers at the Rahmatul Asri Modern Islamic Boarding School, for example, in establishing an Islamic law, especially in the implementation of Worship, are of course all the opinions of the four schools of thought.